VBR traffic control in ATM networks. - Shan, Tong. (University of Ottawa (Canada), 2000)
The VBR traffic control schemes are presented with the objectives of preventing network congestion, supporting end-to-end QoS on per-connection basis, and achieving a high level of resource utilization. First, an admission control algorithm is designed for the real-time VBR Traffic, which performs better than previous ones in terms of both the network bandwidth utilization and the computational time needed. Second, two lossless MLB traffic shapers are designed that can guarantee certain requirements for shaping buffer occupancy or delay bound. Third, the statistical traffic shaping scheme is put forward, and it can achieve a higher level of resource utilization than lossless shaping. Fourth, the impact of rate-controlling on end-to-end QoS is analyzed. Fifth, the guidelines and design criteria on controlling the VBR traffic are provided based on the research results in this thesis.
Keywords: Engineering, Electronics and Electrical.